2013
DOI: 10.1093/humrep/det237
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal specific, selenium-independent GPX5 protects cells from oxidative stress-induced lipid peroxidation and DNA mutation

Abstract: study qustion: Can selenium (Se) independent, epididymal-specific glutathione peroxidase 5 (GPX5) protect CHO-K1 cells from oxidative damage and, more specifically, from lipid peroxidation and DNA mutation?summary answer: CHO-K1 cells expressing GPX5 have increased resistance to oxidative challenge and, more specifically, decreased levels of lipid peroxidation and decreased levels of the downstream DNA lesion 8-oxo-7,8-dihydroguanine (8-oxodG) what is known already: GPX5 associates with sperm during transit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 60 publications
0
38
0
1
Order By: Relevance
“…Since SOD1 quantities did not change due to the tert-BHP treatment, we can conclude that the reabsorption of residual cytoplasm is little or not compromised and thus an active transfer of PRDXs from the epididymal epithelium to the maturing spermatozoa may occur. Although we did not probe a direct transfer of PRDXs to spermatozoa from treated rats, previous evidence strongly suggest this possibility; epididymosomes from bull and humans contain PRDXs3233 and others already demonstrated that proteins can be transferred from epididymosomes to spermatozoa 34353637…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Since SOD1 quantities did not change due to the tert-BHP treatment, we can conclude that the reabsorption of residual cytoplasm is little or not compromised and thus an active transfer of PRDXs from the epididymal epithelium to the maturing spermatozoa may occur. Although we did not probe a direct transfer of PRDXs to spermatozoa from treated rats, previous evidence strongly suggest this possibility; epididymosomes from bull and humans contain PRDXs3233 and others already demonstrated that proteins can be transferred from epididymosomes to spermatozoa 34353637…”
Section: Discussionmentioning
confidence: 69%
“…It is also possible that other antioxidant enzymes may be transferred by epididymosomes, along with PRDXs; these organelles also carry SOD1, thioredoxins, glutathione peroxidase 5 and s-glutathione transferases 3233343537. However, this transfer seems to be well regulated since SOD1 amounts were not augmented in spermatozoa from treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The most realistic function is protection of the sperm during epididymal transit. Several proteins successively secreted in the epididymal fluid may be involved in the reduction of reactive oxygen species in the luminal fluid such as GPX5 (Chabory et al 2010, Taylor et al 2013, thioredoxin, GSTM1-3, SOD1, and PRDX2-5. This protective function may also be illustrated by the presence of several proteins and peptides such as several b-defensins (Yamaguchi & Ouchi 2012), lipocalins, and CRES proteins against bacterial attack .…”
Section: Functions Of the Most Abundant Luminal Epididymal Proteinsmentioning
confidence: 99%
“…In light of this danger caused by SODs, the presence of the epididymal secretory form of glutathione peroxidase (GPX5) which covers the spermatozoa head is noticeable [16,28]. It has been demonstrated that GPX5 protects cells from oxidative stress induced lipid peroxidation and DNA mutation [67], maintains sperm DNA integrity [68] and regulates the synthesis of prostaglandin, key signaling molecules needed by spermatozoa [69]. Therefore, the decrease of GPX5 in the adult F1:Fin rats observed in our study could result in inadequate spermatozoa protection and subsequent dysfunction.…”
Section: Age-related Changes In Expression Of Antioxidant Enzymes In mentioning
confidence: 99%